QUALITATIVE AND QUANTITATIVE ANALYSIS OF PHYTOCHEMICALS IN MARSILEA MINUTA LINN. - A. JOHN DE BRITTO; D. HERIN SHEEBA GRACELIN; D. HERIN SHEEBA GRACELIN; P. BENJAMIN JEYA RATHNA KUMAR (International Journal of Pharma and Bio Sciences, 2013)
The objective of the present study was to find out the presence of phytochemicals in the petroleum ether, benzene, chloroform, methanol and aqueous extracts of Marsilea minuta Linn (Marsileaceae), a common aquatic medicinal fern by both qualitative and quantitative screening methods. In qualitative analysis, the phytochemical compounds such as steroids, reducing sugars, triterpenoids, sugars, alkaloids, phenolic compounds, flavonoids, saponins, tannins, anthroquinones and amino acids were screened in five solvent extracts. The methanol extract of the fern showed positive results for 10 phytochemical tests. The benzene extract exhibited positive results for 9 tests. In chloroform and petroleum ether extracts of the plant showed positive results for 7 tests and in aqueous extract of the fern 5 phytochemical tests were positive. In quantitative analysis the important secondary metabolites such as alkaloids, phenolic compounds, flavonoids, saponins and tannins were tested in all the extracts of the fern. The methanol extract showed highest amount of phytochemicals when compared with other solvent extracts.